Floating Capacitance Multiplier Simulator For Grounded RC Colpitts Oscillator Design - Kartci, Aslihan; Ayten, Umut Engin; Herencsar, Norbert; Sotner, Roman; Jerabek, Jan; Vrba, Kamil (IEEE, 2015)
Actively simulated grounded floating capacitance multipliers have been used in several applications ranging from filter to oscillator design as well as cancellation of parasitic capacitances. In this paper, a new electronically-controllable floating lossless capacitance multiplier (C-Multiplier) circuit is presented, which employs only one Voltage Differencing Current Conveyor (VDCC), one grounded capacitor and one grounded resistor. Since the new simulated C-Multiplier uses a grounded capacitor; accordingly, it is suitable for IC fabrication. A number of simulations with employing commercially available devices through PSPICE program are accomplished to demonstrate the workability, performance, and effectiveness. Functionality of the proposed circuit is verified through its application in a linearly tunable quadrature oscillator, which one is derived from Colpitts oscillator.
Keywords: capacitance multiplier; Colpitts oscillator; quadrature oscillator; voltage differencing current conveyor; VDCC; Engineering